PERAN FILANTROPI DI MASYARAKAT (Studi Analisis terhadap konsep dalam Sistem Ekonomi Sosialisme dan Sistem Ekonomi Syariah) - Chonita Lutfyah; Pamela Vernanda; Annisa Amalia Wati; Devi Rahmadhiyanti; Natasya Samantha; Ani Faujiah (ICO EDUSHA, 2021)
The main purpose of this research is to find out how philanthropy is in the concept of socialist economic system and sharia economic system. This study uses a qualitative descriptive research method with a literature analysis study (library research). There are advantages and disadvantages to this philanthropy for the state. Islamic philanthropy is a term that emerged in modern times as a result of the adoption of the word. This kind of philanthropy activity has taken place before the existence of Islam because the discourse of social justice has developed from before the existence of Islam. In Indonesian, a term that is quite similar to philanthropy is social generosity, which includes zakat, infaq, alms, and waqf (ZISWAF).In theory, the concept of philanthropy as a mechanism for distributing wealth is the activity of diverting a portion of wealth or material assets from those who have a capable economy, to be distributed to those who are less fortunate in their economy. This proves that zakat, infaq, alms, and waqf, or philanthropic institutions are public or social institutions that play a major role in the socio-economic community. Islamic philanthropy (zakat, infaq, alms, and waqf) is a solution to people's problems and humanitarian problems, especially poverty. So the poverty alleviation effort is to develop and manage ZISWAF funds optimally, or by managing funds productively. Through the CSR (Corporate Social Responsibility) program, business actors are not only concerned with profit but also contribute to society such as PT Sido Muncul. Keywords : Philanthropy, Socialist Economic System, Sharia Economic System References Abdiyansyah linge. "Filantropi islam sebagai instrumen keadilan ekonomi"Jurnal perspektif ekonomi darussalam volume 1, nomor 2, September 2015 Donny Prasetyo, Irwansyah, “Memahami Masyarakat dan Prespektifnya”, Jurnal Manajemen Pendidikan dan Ilmu Sosial, Volume 1, Issue 1, Januari2020, Fitra Rizal, Haniatul mukaromah "Filantropi Islam Solusi Atas Masalah Kemiskinan Akibat Pandemi Covid 19" Jurnal hukum dan pranata sosial islam. Vol. 3 No.1 . Januari-juni 2021 Hanik Fitriani.,’’Kontribusi Zakat sebagai Solusi Menghadapi Krisis Ekonomi Dan Keuangan Sosial Islam di Masa Pandemi Covid-19’’, Journal of Islamic Philanthropy and Disaster, Vol 1, No 1 (2021), Ibid, Mansur Efendi.’’,Pengelolaan Filantropi Islam di Tengah Pandemi Covid-19’’, Jurnal Manajemen Zakat dan Wakaf, Volume 2 , No. 1, Tahun 2021, Nur Iman Hakim AlFaqih,S.E.I.,M.E.K.,” Peran Lembaga Filantropi Islam dalam Menanggulangi Turbulensi Ekonomi Masyarakat dalam situasi Pandemi Covid-19’’,Jurnal Ekonomi Islam, Vol:4,No.1,Desember2020, Priyono dan Zainuddin Ismail, “Sosialisme”, 271 Sudirman, "Zakat dalam Pusaran Arus Modernitas" jurnal ekonomi islam dan sosial Vol.3 No.1, Juni 2021 Syamsul Effend, Perbandingan Sistem Ekonomi Islam dan Sistem Ekonomi Kapitalis dan Sosial”, Jurnal Riset Akuntansi Multiparadigma (JRAM) Vol.6, No.2, Desember 2019, Tajudin, Gilang Zulfikar, Mas Fierna Janvierna Lusie Putri, Amrizal, Rulli Hardi, “Menumbuhkan Filantropi antar Sesama”, Jurnal Loyalitas Sosial, Vol.3 No.1 Maret 2021, Tamim, Imron Hadi "Peran Filantropi dalam Pengentasan Kemiskinan Dalam Komunitas Lokal" jurnal sosial islam Vol.1 no.1 (2011) Udin Saripudin, "Filantropi Islam Dan Pemberdayaan Ekonomi", Jurnal Bisnis dan Manajemen Islam, Vol. 4, No. 2, (Desember 2016), 179 Widjaja, Gunawan. 2008. "Resiko Hukum dan Bisnis Perusahaan Tanpa CSR". Jakarta : Penebarswadjaya Dea Duta Aulia, Konsisten Jalankan CSR, Perusahaan Ini Raih Penghargaan Bergengsi dari BISRA 2021, diakses dari https://m.tribunnews.com/amp/bisnis/2021/04/23/konsisten-jalankan-csr-perusahaan-ini-raih-penghargaan-bergengsi-dari-bisra-2021, pada tanggal 9 Desember 2021, pukul 20.30 Zakaria Batubara, “Ekonomi Syariah Sebagai Fondasi Ekonomi Kerakyatan Untuk Mencapai Indonesia Yang Sejahtera”,Iqtishaduna : Jurnal Ilmiah Ekonomi Kita, vol. 01, no. 01, Juni 2012